## p ∧ q ≡ q ∧ pp ∨ q ≡ q ∨ p

### To prove the equality p ∧ q ≡ q ∧ p, we need to show that both sides of the equation are equivalent, meaning they have the same truth value for all possible truth values of p and q

To prove the equality p ∧ q ≡ q ∧ p, we need to show that both sides of the equation are equivalent, meaning they have the same truth value for all possible truth values of p and q.

To do this, we can construct a truth table and evaluate both sides of the equation for all possible combinations of truth values for p and q:

“`

| p | q | p ∧ q | q ∧ p |

|—|—|——-|——-|

| T | T | T | T |

| T | F | F | F |

| F | T | F | F |

| F | F | F | F |

“`

From the truth table, we can see that for all possible combinations of truth values, p ∧ q is equal to q ∧ p. Hence, we can conclude that p ∧ q ≡ q ∧ p is true.

Now let’s prove the equality p ∨ q ≡ q ∨ p:

Again, we will construct a truth table and evaluate both sides of the equation for all possible combinations of truth values for p and q:

“`

| p | q | p ∨ q | q ∨ p |

|—|—|——-|——-|

| T | T | T | T |

| T | F | T | T |

| F | T | T | T |

| F | F | F | F |

“`

From the truth table, we can see that for all possible combinations of truth values, p ∨ q is equal to q ∨ p. Hence, we can conclude that p ∨ q ≡ q ∨ p is true.

In summary, both equations p ∧ q ≡ q ∧ p and p ∨ q ≡ q ∨ p are true, as demonstrated by the truth tables above.

## More Answers:

Proving logical equivalence: p ∧ p ≡ pp ∨ p ≡ pProving the Equivalence of ¬(¬p) and p in Mathematics: Step-by-Step Analysis

Proving Logical Equivalences Using De Morgan’s Laws: A Step-by-Step Guide